GASTROENTERITIS CAUSED BY CONDITIONALLY PATHOGENIC MICROFLORA IN YOUNG CHILDREN (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
About a billion episodes of diarrhea occur in young children every year. Symptoms accompanying acute gastroenteritis include malaise, abdominal pain and cramps, nausea, vomiting and diarrhea, which usually last from 1 to 5 days, but sometimes up to 14 days. Diarrhea caused by opportunistic microflora in children can be associated with various causes. Opportunistic pathogens are usually present in the human body, but under certain conditions they can become pathogenic and cause disease. Here are several possible causes of diarrhea in children associated with conditionally pathogenic microflora. In this case, an imbalance of microorganisms in the intestine occurs, when conditionally pathogenic bacteria begin to predominate over beneficial ones. This pathology is caused by the use of antibiotics, which can upset the balance of microorganisms in the intestine and contribute to the development of diarrhea.